2012
DOI: 10.3923/ijps.2012.251.258
|View full text |Cite
|
Sign up to set email alerts
|

Allometric Growth of Testes in Relation to Age, Body Weight and Selected Blood Parameters in Male Japanese Quail (Coturnix japonica)

Abstract: The Japanese quail is a very valuable animal model for research in a variety of biological disciplines. The purpose of this study was to characterize and interrelate age-dependent testicular parameters with various blood constituents: blood glucose, plasma proteins and packed cell volume that are developing concurrently in the growing bird. Another objective of the study was to identify selective physioanatomical markers for predicting the testicular growth and the onset of sexual maturity. Male Japanese quail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
4
4
2
Order By: Relevance
“…This can be justified by the fact that the latter’s readings were taken on animals younger than ours, as testicular weights and volumes generally increase with age until puberty and reach maximum values at the sexual period [ 9 , 46 ]. The present study showed that the left testis weight is almost always more developed than that of the right testis, which is consistent with previous studies in quails [ 19 ]and birds [ 9 , 45 , 47 ]. The rapid testicular growth in the quails in our trial is thought to be due to the high propagation of Sertoli cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This can be justified by the fact that the latter’s readings were taken on animals younger than ours, as testicular weights and volumes generally increase with age until puberty and reach maximum values at the sexual period [ 9 , 46 ]. The present study showed that the left testis weight is almost always more developed than that of the right testis, which is consistent with previous studies in quails [ 19 ]and birds [ 9 , 45 , 47 ]. The rapid testicular growth in the quails in our trial is thought to be due to the high propagation of Sertoli cells.…”
Section: Discussionsupporting
confidence: 93%
“…The testicular weight noted with the control treatment is higher than those observed by Vatsalya and Kashmiri[ 45 ], but those obtained with the T2 treatment (30%) at 56 days are higher than the latter and those obtained by Wilkanowska et al [ 34 ] on Pharaoh quails. This can be justified by the fact that the latter’s readings were taken on animals younger than ours, as testicular weights and volumes generally increase with age until puberty and reach maximum values at the sexual period [ 9 , 46 ].…”
Section: Discussioncontrasting
confidence: 52%
“…Using a vernier caliper to measure the length and width of testes. The testes volume was calculated by (cm 3 ) according to (Vatsalya & Arora, 2012). A small part of the testis (5g) was taken from each treatment and fixed in Bouin's fluid for 24 hours, then dehydrated in ethanol, cleared in xylene and embedded in paraffin.…”
Section: Testes Parametersmentioning
confidence: 99%
“…This can be explained by the fact that the birds adapted better and better to the substitution of corn by P. biglobosa pulp in their diet. Several authors have reported the same growth pattern in the quail Coturnix japonica (Ikaya et al, 2005;Kizilkaya et al, 2006;Vatsalya & Arora, 2012). The average weekly gain evolved in a decreasing way with the age of the birds.…”
Section: Resultsmentioning
confidence: 73%